Ability Test of C-4-Methoxyphenyl-Calix[4]resorcinarene as An Inhibitor of Calcium Carbonate (CaCO3) Crust Growth at Various Concentration - Utomo, Suryadi Budi; Ramadhani, Lathifah; Hanifah, Kisti Makrifatul; Huda, Zamira Zia’ul; Susanti V.H, Elfi; Ariani, Sri Retno Dwi; Mulyani, Sri; Wathon, Muhammad Hizbul (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
The primary objective of this study was to evaluate the capacity of C-4-methoxyphenyl-calix[4]resorcinarene in impeding the development of CaCO3 crust at varying concentrations of the inhibitor and different durations of contact. The research employed a seeded experimental approach using a 0.1 M CaCO3 growth solution maintained at 80 °C. The concentrations of C-4-methoxyphenyl-calix[4]resorcinarene introduced into the CaCO3 growth solution were 0, 5, 10, 20, and 40 ppm. The experimental procedure commenced with preparing crystal seeds, which is pivotal for gauging crystal growth rates. Results obtained from crystal weighing and morphological analysis through Scanning Electron Microscopy (SEM) indicated that C-4-methoxyphenyl-calix[4]resorcinarene effectively impeded the pace of CaCO3 scaling. The inhibitory efficacy of C-4-methoxyphenyl-calix[4]resorcinarene as a CaCO3 scaling inhibitor was contingent on well-regulated temperature during the heating phase. The inhibition effectiveness was positively correlated with the inhibitor's concentration; higher concentrations yielded superior suppression of CaCO3 scaling. Optimal scale reduction was observed at an inhibitor concentration of 10 ppm during a 20-minute contact period. These findings underscore the promising potential of C-4-methoxyphenyl-calix[4]resorcinarene as a viable inhibitor for mitigating scaling growth rates in various industrial fluid systems and related contexts.